Terminalia catappa leaf extracts inhibited metastasis of A2058 and A375 melanoma cells via downregulating p-Src and β-catenin pathway in vitro - Chang, Chin-Kuo; Chu, Shu-Chen; Huang, Jing-Yang; Chen, Pei-Ni; Hsieh, Yih-Shou (Frontiers in Pharmacology, 2022)
Background: Melanoma is a highly aggressive, lethal, and malignant cancer. Once diagnosed early, it can be easily removed and cured with satisfaction. Although many methods such as surgery, chemotherapy, radiotherapy, and immunotherapy have been used to treat this disease at an advanced stage, the outcomes are poor. Terminalia catappa leaves have been shown to have various biological benefits, including antitumor activity. The specific effects and molecular mechanisms of Terminalia catappa leaf in treating A2058 and A375 melanoma cells in vitro need to be clarified. Methods: The A2058 and A375 melanoma cancer cells were treated with TCE, and then the effect of Terminalia catappa leaf extracts (TCE) on migration and invasion was examined. The cell migration/invasion capacities of A2058 and A375 cells were investigated by a modified Boyden chamber assay. Zymography was used to clarify the activities of matrix metalloproteinases-2 (MMP-2) and u-PA. We performed a Western blot to verify the related expression of phospho-Src (Tyr416), phospho-FAK (Tyr397), Vimentin, and β-catenin. Results: Modified Boyden chamber assays demonstrated that TCE treatment significantly inhibited A2058 and A375 cell migration/invasion capacities. In the zymography results, we showed that TCE negatively modulated the activities of MMP-2 and u-PA. Western blot indicated that TCE reduced the expression of phospho-Src (Tyr416), phospho-FAK (Tyr397), Vimentin, and β-catenin. Conclusions: TCE affected the antimetastasis of the A2058 and A375 melanoma cell lines by inhibiting the FAK/Src interaction and Wnt/β-catenin pathways in vitro. TCE may serve as a powerful chemopreventive agent against metastasis of melanoma cancer.